Hemispheric Asymmetry and Stress Exposure Model in a Professional Evaluation Situation - Gryazeva-Dobshinskaya, V; Dmitrieva, Y; Korobova, S (KnE Life Sciences, 2018)
The urgency of the study on the system of psychophysiological and psychological (temperamental and personal) factors of stress exposure in a situation of professional evaluation of the subjects is considered. The results of the empirical study of stress factors including psychophysiological, temperological and personal characteristics of the subjects are given. The analysis is made with the use of hardware–software system ‘Aktivatsiometr 9К’ by Y.А. Tsagarelli to detect psychophysiological parameters (functional hemispheric asymmetry, activation of the brain hemispheres, strength and lability of the nervous system), «Structure of temperament questionary» by V.М. Rusalov, and diagnosis of the strategic options for choosing a life journey of the ‘Typology of Personal Choice’ by V.G. Gryazeva-Dobshinskaya and A.S. Maltseva. Individually typological, as well as dynamic and activity-situational (in a situation of professional evaluation) characteristics of activation and hemispheric asymmetry of the subjects are calculated. Stress reaction is detected, provided individual-typological and activity situational characteristics of activation of the subjects differ by more than 1.5 times. Fifty-six senior students aging between 20 and 25 are the sample of the analysis. The sample is divided into two groups in accordance with the response to the situation of assessment of professional competence: group 1 (n1 = 19 people) with a detected stress reaction, group 2 (n1 = 37 people), in which the stress reaction is not detected. The correctness of the obtained differentiation in the groups of students, differing in the system of indicators of psychophysiological, temperological and personal characteristics is proved with the help of discriminate analysis. The model of stress exposure in a situation of professional evaluation is developed. Keywords: functional hemispheric asymmetry, everyday stress, professional evaluation, temperamental characteristics, personal choice